2006
DOI: 10.1126/science.1125949
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging in Cancer

Abstract: Medical imaging technologies have undergone explosive growth over the past few decades and now play a central role in clinical oncology. But the truly transformative power of imaging in the clinical management of cancer patients lies ahead. Today, imaging is at a crossroads, with molecularly targeted imaging agents expected to broadly expand the capabilities of conventional anatomical imaging methods. Molecular imaging will allow clinicians to not only see where a tumor is located in the body, but also to visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
826
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,023 publications
(832 citation statements)
references
References 85 publications
4
826
0
2
Order By: Relevance
“…In addition, we used the contrast ratio (tumor to muscle) to confirm the clearance of MitDt‐1. If the ratio exceeds 2.5, it means that relatively more MitDt‐1 remains in the tumor (Figure 5D) 15, 27. As a result, it was found that the concentration ratio (tumor to adjacent muscle) was 3.94 ± 0.44; and thus it was confirmed that the MitDt‐1 was localized within tumor sites due to TPP.…”
Section: Resultsmentioning
confidence: 82%
“…In addition, we used the contrast ratio (tumor to muscle) to confirm the clearance of MitDt‐1. If the ratio exceeds 2.5, it means that relatively more MitDt‐1 remains in the tumor (Figure 5D) 15, 27. As a result, it was found that the concentration ratio (tumor to adjacent muscle) was 3.94 ± 0.44; and thus it was confirmed that the MitDt‐1 was localized within tumor sites due to TPP.…”
Section: Resultsmentioning
confidence: 82%
“…Combined with new NIR-labeled biomarkers, these will expand the clinical options available for cancer management in the near future. Several excellent reviews describe the use of targeted markers in animal studies [7] and [67].…”
Section: Discussionmentioning
confidence: 99%
“…Until today detection of a tumor by MRI, PET or ultrasound imaging is limited by its minimal size of 1 cm in diameter. 50 Molecular imaging is becoming increasingly important in cancer diagnosis by using cancer specific target based imaging probes. Using probes coupled to fluorescent dyes or radioisotopes in vivo had been applied in preclinical models.…”
Section: Potential Use Of F16 For Radionuclide Therapymentioning
confidence: 99%